2002
DOI: 10.1080/165019702317242640
|View full text |Cite
|
Sign up to set email alerts
|

Improved client participation in the rehabilitation process using a client-centred goal formulation structure

Abstract: The aim was to evaluate whether the use of a client-centred instrument, the Canadian Occupational Performance Measure (COPM), affects the patients' perception of active participation in the rehabilitation process. The study included 155 patients in the experiment group and 55 in the control group, within geriatric, stroke, and home rehabilitation. The COPM was used in the experiment group. A structured interview was performed within 2-4 weeks after discharge with 88 patients in the experiment group and 30 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
131
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(147 citation statements)
references
References 22 publications
9
131
0
4
Order By: Relevance
“…Also, individuals are able to manage more tasks after the completion of rehabilitation if a client-centred approach has been adopted. 5 The use of a measure where the individuals explicitly identify their problems and treatment goals has been highlighted as one of the four key elements of a client-centred approach to rehabilitation practice. 3 Studies report that therapists typically rely on informal methods to engage an individual in problem identification and goal setting; however, the use of formal measures has been advocated.…”
Section: Introductionmentioning
confidence: 99%
“…Also, individuals are able to manage more tasks after the completion of rehabilitation if a client-centred approach has been adopted. 5 The use of a measure where the individuals explicitly identify their problems and treatment goals has been highlighted as one of the four key elements of a client-centred approach to rehabilitation practice. 3 Studies report that therapists typically rely on informal methods to engage an individual in problem identification and goal setting; however, the use of formal measures has been advocated.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 This leads to closer adherence to the training, to more effort of patients to use the skills in daily life and to maintain these activities after finishing the training, inducing an improved rehabilitation outcome. 19,20 Second, in ToCUEST, specific goals were formulated, which were analyzed and trained, combining principles of motor learning with principles of training physiology. 3 The importance of a task-oriented intensive training was emphasized in ToCUEST, as well as the shift from a multi-to an inter-or trans-disciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a strong emphasis that the person on sick leave should participate in the rehabilitation planning (Millet and Sandberg, 2003;Wressle et al, 2002), there has been little research on this topic. Söderberg et al, 2004 showed that the common work rehabilitation goals expressed by the clients were ignored and that the clients in the study perceived themselves as abandoned after the rehabilitation period.…”
Section: Introductionmentioning
confidence: 99%